Investigating the effect of nanomaterials on the Marshall properties and durability of warm mix asphalt - Aljbouri, Rawaa Q.; Albayati, Amjad H. (Cogent engineering, 2023)
Warm mix asphalt (WMA) has gained significant interest recently as a more sustainable and environmentally friendly alternative to conventional hot mix asphalt (HMA). WMA is produced at lower temperatures, reducing energy consumption and greenhouse gas emissions. However, there is an ongoing need to improve the durability of WMA to satisfy the expanding demands of modern road infrastructure. Nanomaterials that possess unique characteristics of high surface area and reactivity could serve as promising additives for improving the performance of WMA. This research aims to investigate the effect of four nanomaterial types on the Marshall properties and durability of warm mix asphalt (WMA). These types are; nano silica $\left({{\rm{NS}}} \right)$ N S , nano carbonate calcium $\left({{\rm{NCC}}} \right),{\rm{ }}$ N C C ,